Exploiting Intellectual Capital to Increase its Contribution to Sustainable Development from the Point of View of Academics at the Iraqi University (Zien Journal of Social Sciences and Humanities, 2022)
The study aimed to identify the role of intellectual capital management and the requirements of sustainable development in universities, and to identify the determinants and difficulties faced by intellectual capital and their relationship to sustainable development. The researchers used descriptive analytical method for its relevance to this study. A set of questionnaire was developed to collect data from the study population. The most important results obtained were: The intellectual capital training contributes significantly and effectively to creating new teaching methods at the university, as it is an important factor for the transfer and exchange of experiences and knowledge. The diversity of educational programmers at the university contributed to the process of sustainable development. University intellectuals participated in seminars held by organizations that concern about sustainable development, and in specialized forums to acquire about almost everything that is new in the world of knowledge. The university's strategies in the field of sustainable development are not clear, and that it does not attract human elements who have experience in the field of strategic planning for sustainable development, and The university has little information that is characterized by accuracy on the subject of sustainable development and the lack of clear and specific standards and criteria to measure its intellectual capital. The study made several important recommendations, the most important of which were: The need for the university administration to pay attention to the method of teamwork and the participation of employees in it when making decisions that concern them. The university needs to set clear scientific standards to measure and evaluate its intellectual capital and to focus on training programmers aimed at sustainable development. In addition, it needs to add specialized scientific courses for sustainable development within its educational programmers, and that the university administration should develop clear strategic plans based on principles of sustainable development.